Characterizing behavior change techniques used in the self-management of binge eating and weight: Applying a user-centered design approach. (January 2022) - Fu, Emily; Neubert, Sarah W.; Chang, Angela; Smith, J.D.; Graham, Andrea K.
Abstract: User-centered design methods aim to increase intervention engagement by focusing on consumers' needs and preferences. We conducted a needs assessment (the first step in user-centered design) via a digital diary study to understand how individuals with recurrent binge eating (≥12 episodes in 3 months) and obesity (BMI ≥30 kg/m 2 ) manage these problems in their day-to-day lives and the approaches they use to change their behavior. Specifically, we applied the Behavior Change Technique (BCT)-Taxonomy to characterize which standardized BCTs individuals use to change binge eating and health-related behaviors and their motivations to use them, to inform the design of a mobile intervention. We analyzed qualitative data from 22 adults (64% female, 32% White) who submitted 176 diary entries. For each entry, we coded the BCTs used, motivation for use, and whether the BCT(s) were perceived as beneficial for behavior change. Across participants, investigators identified 50 of the 93 standardized BCTs (54%). Each participant used an average of 12 ( SD  = 4) BCTs, most commonly Behavior Substitution (72.3%), Distraction (68.2%), Goal Setting ( Behavior ) (63.6%), Action Planning (59.1%) and Adding Objects to the Environment (59.1%). More BCTs were coded as beneficial (49%) versus detrimental (24%) or neutral (27%). Techniques were most commonly motivated by preventing binge eating (95.5%), losing weight (95.5%), reducing unhealthy food choices (90.9%), or managing stress (59.1%). Results help inform how interventions could be designed to support consumers in changing binge eating and weight-related behaviors, although such designs would need to be tested for their impact on engagement and outcomes. Highlights: User-centered design can inform optimization of behavioral interventions. We assessed how people manage recurrent binge eating and weight in daily life. We coded behavior change techniques (BCTs) used to manage binge eating and obesity. Common BCTs in our sample were not always deemed beneficial for behavior change. Common motivations for using BCTs were to improve eating and manage stress.